The Effect of Gist Strategy on Students’ Achievement in Reading Comprehension - Rejoice Agape Sinuraya; Pandoyo Situmorang; Robinson Pangihutan Sihombing; Rodolfo Josafat Gultom; Kartina Rahmadhani Rambe (Universitas Pahlawan Tuanku Tambusai, 2021)
This study focuses on the effect of the GIST strategy on the reading comprehension of SMK Sinar Husni BM Labuhan Deli students. This study aims to find ways to improve students' reading comprehension through basic strategies. Lack of student knowledge of what the text says about it. The design of experiments was used in this study. The author taught two different classes at SMK Sinar Husni BM Labuhan Deli. They were a control class and an experimental class. The population of this study is 50 students consisting of two classes. Data is collected through reading comprehension tests. The author uses two tests. There are pre-test and post-test. By using the experimentally guided GIST strategy, the reading comprehension of the students after treatment was improved. The results of this study show that The Effect of GIST Strategy in Improving Students’ Reading Comprehension